PROBLEMIC’ METHODOLOGY IN THE TEACHING OF MATH - Maurtua Aguilar, José Luis (2014)
The main objective is to contribute with the development of methodological proposals of didactic performance based on the ones which support students’ (mainly the ones from high school) independent activity as well as the active participatory methods that contain the problemic method and the heuristic method to cite a few, which basically favor the development of the creativity in the resolution of problems of a math and on daily issues.